2017
DOI: 10.1093/annonc/mdx350
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping unmet supportive care needs, quality-of-life perceptions and current symptoms in cancer survivors across the Asia-Pacific region: results from the International STEP Study

Abstract: Health care systems in Asian countries need to re-think and prioritize survivorship cancer care and put action plans in place to overcome some of the challenges surrounding the delivery of optimal supportive cancer care, use available resource-stratified guidelines for supportive care and test efficient and cost-effective models of survivorship care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 25 publications
9
82
5
Order By: Relevance
“…Studies that used multivariate models to identify the factors associated with higher levels of unmet needs most commonly reported that younger patients had more unmet needs (Table ). This was reported in six studies (Brennan et al, ; Harrison et al, ; Molassiotis et al, ; Rowlands, Janda, McKinnon, Webb, & Beesley, ; Santin et al, ; Smith et al, ) and is thus recognised as strong evidence. Three other authors did not find this association (Bender et al, ; Hodgkinson, Butow, Fuchs, et al, ; Willems et al, ).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Studies that used multivariate models to identify the factors associated with higher levels of unmet needs most commonly reported that younger patients had more unmet needs (Table ). This was reported in six studies (Brennan et al, ; Harrison et al, ; Molassiotis et al, ; Rowlands, Janda, McKinnon, Webb, & Beesley, ; Santin et al, ; Smith et al, ) and is thus recognised as strong evidence. Three other authors did not find this association (Bender et al, ; Hodgkinson, Butow, Fuchs, et al, ; Willems et al, ).…”
Section: Resultsmentioning
confidence: 84%
“…Inconsistent evidence was observed for the time since treatment/diagnosis, the stage of the disease at diagnosis, and depression. While two studies reported that survivors for whom less time had passed since the diagnosis/treatment had more unmet needs (Cheng et al, ; Molassiotis et al, ), the majority concluded that time since treatment/diagnosis was unrelated to unmet needs (Hodgkinson, Butow, Fuchs, et al, ; Hodgkinson, Butow, Hunt, Pendlebury, Hobbs, & Wain ; Willems et al, ). In terms of a more advanced stage of disease, two studies reported a relationship to unmet needs (Hodgkinson, Butow, Fuchs, et al, ; Rowlands et al, ), while one could not confirm these findings (Urbaniec et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6] Many have long-term residual symptoms, with more than half of early-stage survivors reporting five or more symptoms of at least moderate severity 12 months after diagnosis, 7 and fatigue, loss of strength, pain, sleep disturbance and weight changes up to five years after diagnosis. 8,9 Cognitive impairment, fatigue and other symptoms can affect independent functional ability and return to work, decreasing financial security. 10,11 Other common physical long-term treatment effects include sexual dysfunction, infertility and chemotherapy-induced peripheral neuropathy.…”
Section: With Advances In Cancer Screeningmentioning
confidence: 99%
“…12 Late-term effects include second malignancies, and impaired cardiac and pulmonary function. 12 Fear of cancer recurrence occurs in approximately 70% of survivors, with approximately 50% reporting fear of at least moderate severity, 13 high levels of uncertainty about the future, 8 and unmet needs focused on fear of relapse. 14 Changes in social roles, support networks and family and intimate relationships often occur, creating added distress.…”
Section: With Advances In Cancer Screeningmentioning
confidence: 99%
“…38 Information about IO is in the top 5 unmet needs for cancer survivors. [53][54][55][56][57] It is estimated that less than one-fifth of cancer patients and survivors who use TCIM have done so at the recommendation of a medical practitioner. 58 For those patients who have heard about TCIM, many seek to have an informative discussion about use and prefer to access these services from a practitioner skilled in treating patients with cancer.…”
Section: Discussionmentioning
confidence: 99%